Tomb groups from the necropolis of Coseanetto (UD): Characteristic forms and contexts in a small rural community - Mandruzzato, Luciana; Cividini, Tiziana (Rei Cretariae Romanae Fautorum Acta, 2015)
The rural necropolis of Coseanetto (Coseano-UD) is situated in the north-western part of the upper Friuli plain, not far from the first slopes of the Tilaventino morainic amphitheatre and about 300 m away from the Roman settlement to which it was related (dated between the half of the 1st century BC and the 5th century AD).